Zimbabwe`s reengagement with the United Kingdom after the new political dispensation - Mafumo Patience (BUSE, 2019)
The relations between Zimbabwe and the United Kingdom took a nose dive following the fast track land reform programme which disposed white commercial farmers of their land. This subsequently resulted in United Kingdom imposing sanctions on Zimbabwe which impacted negatively on Zimbabwe`s political and economic fortunes. The United Kingdom also felt the heat of bad relations with its former colony and the two nations have been making efforts to reengage for mutual benefit of the two nations. This research was focused on understanding Zimbabwe`s reengagement efforts with the United Kingdom after the new political dispensation. The study employed qualitative research methodology, with primary data being collected through semi structured interviews, while secondary data was gleaned from published books, journal articles, reviews and newspaper articles published in print and online. From the British perspective for reengagement to succeed the Zimbabwe government must institute political and economic reforms that would attract foreign direct investments. The research noted that the British acknowledge efforts by the Zimbabwe government in initiating reforms notably repeal of POSA and AIPPA as a move in the right direction. However there are some sticking points in as far as political reforms are concerned citing too much interference of the military and other security agencies in suppressing demonstrations. The study also noted that from the Zimbabwean government the British were not sincere as they are making unreasonable demands aimed at effecting regime change. According to the research findings it can be concluded that the reengagement process is going to take a long period of time to bear fruits economically. The research therefore recommended that the Zimbabwe government should deal with the internal reforms so as to give impetus to the reengagement .The study also recommended that Zimbabwe must maintain the Look East Policy as a back up plan in case reengagement with the United Kingdom does not bear fruits